Estimating the impacts of climate change on the habitat suitability of common minke whales integrating local adaptation - Sun, Bin; Zhao, Linlin; Shao, Fei; Lu, Zhichuang; Tian, Jiashen; Liu, Changdong (Frontiers in Marine Science, 2022)
Whales have irreplaceable roles in maintaining marine ecosystem services while also experiencing serious anthropologic and climate change stresses. Common minke whales (Balaenoptera acutorostrata) have suffered intense harm by commercial whaling, and the recovery of this species is likely to be imperiled by climate change. To better manage and conserve this species, it is important to predict the current potential habitat distributions as well as those under future climate change scenarios. Such prediction is typically fulfilled by species distribution models (SDMs), which build the correlation between species occurrence data and its habitat environmental variables. SDMs are commonly constructed at the species level, assuming the homogenous response of species to climatic variables along their whole geographical range. Spatially segregated populations (subspecies, lineages) from the same species inhabit distinct environmental conditions and gradually adapt to respective local conditions, resulting in niche differentiation among populations. Species-level SDMs that ignore local adaptation would mask the different responses of populations to climate change and might present an unrealistic picture of potential species distributions. Based on the morphology and genetics evidence, the common minke whale was divided into three populations (subspecies), including the North Atlantic population (NAP), Southern Hemisphere population (SHP) and North Pacific population (NPP), which inhabited isolated geographical areas with distinct environmental conditions. We quantified the realized niches of these populations and found significant ecological niche differentiation among them. We then constructed SDMs at the species and population levels, comparing the predictive results from these two types of models under different climate change scenarios. The two types of models projected a similar change trend for species range, with a contraction of suitable habitats for the NAP and SHP and an expansion for the NPP in the future. However, the magnitudes of change were different, and the population-level model outputted more optimistic results for the SHP and NAP, indicating less habitat loss. This study highlighted the importance of considering local adaptation in estimating the climate impact on species habitat suitability. The spatiotemporal predictions of habitat suitability provide essential knowledge for designing climate-adaptive conservation and management strategies, such as the delimitation of mobile marine protected areas (MPAs).